2011
DOI: 10.1088/0953-4075/44/19/191001
|View full text |Cite
|
Sign up to set email alerts
|

Fourier photospectroscopy of Xe@C60through a Xe 4dresonance window: theory versus recent experiment

Abstract: The photoionization cross section of endohedral Xe@C60 over a Xe 4d giant resonance energy region, calculated in the time-dependent local density approximation, is compared with recent measurements (Kilcoyne et al 2010 Phys. Rev. Lett. 105 213001). An analysis based on the Fourier transforms of oscillatory cross sections is performed to derive a number of inherent similarities between the prediction and the data, including a large beating-type oscillation and several others of intermediate size. Results stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
2
12
2
Order By: Relevance
“…However, we note that the photoelectron spectroscopy experiment of Rüdel et al [11] indicates a larger C 60 width of ∼3 a.u. A recent study [12] has also found indications of a 3-a.u. width in the experiment of Kilcoyne et al [2].…”
Section: Introductionmentioning
confidence: 83%
“…However, we note that the photoelectron spectroscopy experiment of Rüdel et al [11] indicates a larger C 60 width of ∼3 a.u. A recent study [12] has also found indications of a 3-a.u. width in the experiment of Kilcoyne et al [2].…”
Section: Introductionmentioning
confidence: 83%
“…Nonetheless, it has been shown that these difficulties are relatively minor [72]. Furthermore, it has also been shown that the experimental data are consistent with the potential having rather sharp (although not discontinuous) edges [73]. Nevertheless, smoother interaction potentials for the endohedral atoms have been proposed to avoid possible problems.…”
Section: Model Potentialsmentioning
confidence: 99%
“…Using the Fourier transform technique, a number of similarities and differences between the theoretical and experimental data were obtained in the work of [73].…”
Section: Using Jellium Models Including Shell Electronsmentioning
confidence: 99%
“…Although giant dipole resonances (GRs) in atoms and condensed matter have been studied intensively, [3,4,5,6] they have attracted a renewed interest in recent years. [7,8,9,10,11,12,13] Owing to the availability of highly intense synchrotron radiation and advanced experimental setups, new materials can be studied in which resonating atoms are embedded into fascinating complex environments like endohedral fullerenes or silicon based clathrates.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed their findings showed reasonable agreement with calculations concerning oscillatory cross section by analysis in the Fourier reciprocal space. [8] Despite the extensive search for modulations of the GR by confinement effects as predicted by Luberek and Wendin, [17] experimental evidence of such modulations remains controversial. It was pointed out by Korol et al [25] that the displacement of the resonating atom within the cage due to either a static displacement, i.e.…”
Section: Introductionmentioning
confidence: 99%